PsycEXTRA Dataset 2001
DOI: 10.1037/e596542007-001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Arrest on Intimate Partner Violence: New Evidence From the Spouse Assault Replication Program

Abstract: Issues and Findings Discussed in this Brief: An analysis of 4,032 incidents in which males assaulted their female intimate partners, comparing the number of repeat offenses when batterers are and are not arrested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 6 publications
5
125
0
Order By: Relevance
“…Trends in domestic violence rates over the past 10 years have documented a decrease and it appears new social norms regarding domestic violence may have emerged (see Klein et al, 1997), which suggest a relation between domestic violence policies and underlying social norms. Alternatively, there has been much research examining the effectiveness of arrest policies (Berk & Newton, 1985;Buzawa & Austin, 1993;Feder, Jolin, & Feyerherm, 2000;Maxwell, Garner, & Fagan, 2001;Schmidt & Sherman, 1993;Sherman & Berk, 1984;Tolman & Weisz, 1995) and some research examining the effects of varying prosecutorial policies (Davis, Smith, & Nickels, 1998;Fagan, Friedman, Wexler, & Lewis, 1984;Feder et al, 2000;Ford & Regoli, 1993); however, this research has revealed mixed results (Maxwell, Garner, & Fagan, 2001). For example, some studies have shown arrest to be an effective deterrent against future offending (Berk & Newton, 1985;Sherman & Berk, 1984), whereas other studies indicate arrest is effective only for a certain profile based on offender characteristics (e.g., employed, White, and Hispanic; Schmidt & Sherman, 1993).…”
Section: Theoretical Perspectives On Policies and Social Normsmentioning
confidence: 99%
“…Trends in domestic violence rates over the past 10 years have documented a decrease and it appears new social norms regarding domestic violence may have emerged (see Klein et al, 1997), which suggest a relation between domestic violence policies and underlying social norms. Alternatively, there has been much research examining the effectiveness of arrest policies (Berk & Newton, 1985;Buzawa & Austin, 1993;Feder, Jolin, & Feyerherm, 2000;Maxwell, Garner, & Fagan, 2001;Schmidt & Sherman, 1993;Sherman & Berk, 1984;Tolman & Weisz, 1995) and some research examining the effects of varying prosecutorial policies (Davis, Smith, & Nickels, 1998;Fagan, Friedman, Wexler, & Lewis, 1984;Feder et al, 2000;Ford & Regoli, 1993); however, this research has revealed mixed results (Maxwell, Garner, & Fagan, 2001). For example, some studies have shown arrest to be an effective deterrent against future offending (Berk & Newton, 1985;Sherman & Berk, 1984), whereas other studies indicate arrest is effective only for a certain profile based on offender characteristics (e.g., employed, White, and Hispanic; Schmidt & Sherman, 1993).…”
Section: Theoretical Perspectives On Policies and Social Normsmentioning
confidence: 99%
“…The need for more experiments in more countries on policing domestic abuse grows greater as the evidence from the US trials gets more worrisome. While the initial US results were encouraging (Sherman and Berk 1984), or at least equivocal (Maxwell et al 2001), longer-term evidence now suggests that for at least one population (urban AfricanAmerican women victims), the policy of mandatory arrest may cause a 100% increase in premature death from all causes among victims whose abusers are arrested (Sherman and Harris 2015).…”
Section: Introduction: Evidence On Policing Domestic Abusementioning
confidence: 99%
“…The replications varied in procedures, comparison interventions, follow-up times, and outcome, leading some to comment that firm conclusions about the effects of arrest cannot be drawn (e.g., Garner, 1997;Garner, Fagan, & Maxwell, 1995). Combining data from all five replication attempts, Maxwell, Garner, and Fagan (2001) concluded that arrest slightly reduced recidivism (i.e., violence against the partner or property, verbal threats of violence), but survival curves for arrested versus nonarrested suspects were nearly identical during 1,000 days of follow-up. After a flurry of empirical interest in the 1980s, the effects of arrest on wife assault recidivism remain unknown.…”
mentioning
confidence: 99%